Immunological Mechanisms Responsible for Radiation-Induced Abscopal Effect - Rodríguez-Ruiz, María E.; Vanpouille-Box, Claire; Melero, Ignacio; Formenti, Silvia Chiara; Demaria, Sandra (Trends in immunology, 2018)
Radiotherapy has been used for more than a hundred years as a local tumor treatment. The occurrence of systemic antitumor effects manifesting as regression of tumors outside of the irradiated field (abscopal effect) was occasionally observed but deemed too rare and unpredictable to be a therapeutic goal. This has changed with the advent of immunotherapy. Remarkable systemic effects have been observed in patients receiving radiotherapy to control tumors that were progressing during immune checkpoint blockade, stimulating interest in using radiation to overcome primary and acquired cancer resistance to immunotherapy. Here, we review the immunological mechanisms that are responsible for the ability of focal radiation to promote antitumor T cell responses that mediate tumor rejection and, in some cases, result in systemic effects. Tumor-targeted radiation occasionally elicits immune-mediated systemic tumor regression. Evidence of synergy between radiotherapy and immune checkpoint blockade (ICB) supports the concept of in situ vaccination by radiation, and ICB combinations together with an optimization of the radiation dose and fractionation offer paths to improved responses. Radiation alters the balance between immune-activating and -suppressive signals in the tumor microenvironment. Pathways involved in autoimmunity and microbial immunity are responsible for regulating the induction of type I interferon via cGAS/STING in irradiated tumors and are stimulated upon tumor cell irradiation and activation of the DNA damage response.